(untitled) (مجلة المنصور, 2025)
Since the twentieth century, dystopian novels have regularly examined the association between mankind and surveillance. With the advance of technology, especially after the industrial revolution, technological devices were highly employed in surveillance. Surveillance is inherently political as various governmental institutions (agencies) use it to create docile, conformed bodies in order to enhance and sustain their control over individuals. This article attempts to examine the representation of surveillance and totalitarian societies in the dystopian novel 1984. Through this novel, George Orwell takes each of the anti-utopian characteristics to its extreme to be a debatable topic in literary and social theories for centuries. The totalitarian government in the novel exerts ultimate control over citizens, both mentally and physically through comprehensive and covert surveillance. Panopticism, a theory proposed by Jeremy Bentham and developed by Michel Foucault, is used to examine Orwell's work. to demonstrate how the party's surveillance methods are similar to the Panoptic prison's surveillance system. The main objective of this article is to show how certain elements of Panopticism are able to deconstruct the idea of privacy in George Orwell's 1984 and how internalized surveillance can influence society in general and the psyche of each individual in particular.